IMPLEMENTASI RONDE KEPERAWATAN DALAM UPAYA MENINGKATKAN PENGETAHUAN PERAWAT - Anggi Regita , Bella; Elasari, Yunina; Yeni Wulandari , Rizki (Jurnal LENTERA, 2025)
One of the things that can cause the healing process to take longer is a nurse's lack of knowledge performing nursing rounds, which can lead to subpar medical care. Ignoring nursing rounds puts patients at risk for physical dysfunction, life-threatening conditions, and worsening of the illness. Situations such as these have the potential to harm patients because they make nursing service providers less professional and provide lower-quality care. The objective of this activity is to find out and optimize the implementation of nursing rounds.The methods used in this activity include assessment, analysis of study results, implementation and evaluation of activities. A nursing management problem was found, namely that the implementation of nursing rounds was not optimal. The review and analysis of the study results was carried out on February 12 - March 9 2024. Implementation and evaluation regarding nursing round education was carried out on April 3 2024.According to the implementation findings, every nurse in the Siger room participated in the activity and had pre- and post-test scores between 60 and 75 and 85 and 95, respectively. It is intended that nurses will be dedicated to carrying out nursing rounds in compliance with SOPs for actions conducted in line with the available SOPs for nursing rounds.